ANALISA PENGARUH BIAYA OPERASIONAL DAN PENDAPATAN TERHADAP KINERJA KEUANGAN BERDASARKAN RASIO RETURN ON ASSET (ROA) PADA PERUSAHAAN JASA KONSTRUKSI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015 – 2017 - Maya Widyana Dewi; Indra Lila Kusuma (ITB AAS INDONESIA, 2019)
ABSTRACT This study aimed to determine whether or not the effect of operating expense and revenue financial performance on construction services companies listed on the Indonesia Stock Exchange (BEI) in 2015-2017. In this study, there are three variables, they are operational (X1), the revenues (X2), and ROA (Y). The research method that used is quantitative method. The samples used by researchers is the Return on Assets (ROA) of the construction services company's operating and revenue in the period 2015-2017. This study uses annual financial statements on construction services companies in the period 2015-2017. Kind of data are secondary, The data collection techniques by means of documentation. Data analysis techniques using multiple linear regression analysis by SPSS version 16.0. Hypothesis test is done by using F-test, t-test, and coefficient of determination. While classical assumption test used this research is normality test, auto correlation test, multicollinearity test, and heteroscedasticity test. The conclusion of this research is that the coefficient of determination operational and revenue affect Return on Assets (ROA) can be saw by R for 26 % and hile the the remaining 94% is influenced by other factors that not examined in this study. So simultaneous operational and revenue has no effect on ROA. Keywords : : operating expense, revenue , ROA (Return On Asset).